Method for detecting arteriosclerosis and cancer using DHPS gene as indicator - NAKAMURA RIKA; HIWASA TAKAKI; SAEKI NAOKATSU; TOMIYOSHI GO; KURODA HIDEYUKI; TAKIGUCHI MASAKI (2020)
The present inventors found that a deoxyhydroxyputrescine lysine synthase (DHPS) gene associated with prostate cancer or cervical cancer has been reported in the past, is surprisingly very well associated with arteriosclerosis and digestive system cancer, and can be used as a desired marker for arteriosclerosis and digestive system cancer. Specifically, the present invention provides a method fordetecting arteriosclerosis and digestive system cancer in a subject, in which the expression of deoxyhydroxyputrescine synthase genes in a test sample, preferably a blood subject, is confirmed in thetest sample, and the arteriosclerosis and digestive system cancer of the subject are detected using the hyperfunction of the gene expression as an indicator. 本发明人发现，以往被报告与前列腺癌或子宫颈癌关联的脱氧羟腐胺缩赖氨酸合酶(DHPS)基因，令人惊讶地，与动脉硬化及消化系统癌非常良好地关联，能作为期望的动脉硬化及消化系统癌的标志物使用，完成本发明。具体而言，本发明提供在所述受试试样中确认在受试试样、优选为血液受试体中的脱氧羟腐胺缩赖氨酸合酶基因的表达，以所述基因表达的亢进作为指标检测受试者的动脉硬化及消化系统癌的动脉硬化及消化系统癌的检测方法。